Potensi Manusia Dan Relevansinya Terhadap Pengembangan Kualitas Generasi Muda - Abadiyah, Sa`adatul (Jurnal Kajian Pendidikan Islam, 2022)
Humans born into the world have been given the gift of potentials that can be actualized by interacting with the natural environment. These potentials include physical potential, spiritual potential, intellectual potential and social potential. These potentials which are brought from birth need to be actualized and optimized well. So that human resources can perform their best performance. One of the most important human resources is the young generation because they are in productive time . The development of the quality of human resources of a nation greatly determines the development of the nation. Indonesia as a developing country has and will continue to do various ways to improve the quality of human resources in realizing a better life. Indonesia, especially with its young generation has potential resources to support the success of nation building. This paper is a thought about how human potentials can be actualized and optimized and its relevance to the development of the quality of young people according to the Islamic perspective.